Donkey milk as a supplement in infant formula: benefits and technological challenges - Souroullas, Kallis; Aspri, Maria; Papademas, Photis (My University, 2018)
The aim of this review paper is to assess the applicability of donkey's milk to infants suffering from Cow Milk Protein Allergy (CMPA) compared to human and other available milk types. The bioactive and immune-supportive character which could be beneficial as a fortifier to the formula-fed infants is described while limitations of this type of milk are also discussed. Studies showed that human and donkey's milk have similar, overall, chemical composition as well as protein homogeneity and antigenic similarities. Several in vitro and in vivo studies showed that donkey's milk has nutraceutical and functional properties that can support immunity, alter metabolism and beneficially modify gut microbiota. Clinical studies illustrated that donkeys' milk is well tolerated (82.6%–88%) by infants. Finally, the effect that processing (i.e. thermal, non-thermal treatments, drying methods) has on donkey milk components is also discussed pointing out the need for minimally processing this type of milk.
Keywords: Lysozyme; Cow's milk protein allergy (CMPA); Immunity; Hypoallergenic; Donkey milk; Non-thermal treatments